Jitter in photon-number-resolved detection by superconducting nanowires - Sidorova, Mariia; Schapeler, Timon; Semenov, Alexej D.; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (APL Photonics)
By analyzing the physics of multi-photon absorption in superconducting nanowire single-photon detectors (SNSPDs), we identify physical components of jitter. From this, we formulate a quantitative physical model of the multi-photon detector response that combines the local detection mechanism and local fluctuations (hotspot formation and intrinsic jitter) with the thermoelectric dynamics of resistive domains. Our model provides an excellent description of the arrival-time histogram of a commercial SNSPD across several orders of magnitude, both in arrival-time probability and across mean photon number. This is achieved with just three fitting parameters: the scaling of the mean arrival time of voltage response pulses, as well as the Gaussian and exponential jitter components. Our findings have important implications for photon-number-resolving detector design, as well as applications requiring low jitter, such as light detection and ranging (LIDAR).
Keywords: Jitter; PNR; SNSPD

Mg dopants in lithium niobate: Defect models and impact on domain inversion - Bocchini, Adriana; Rüsing, Michael; Bollmers, Laura; Lengeling, Sebastian; Mues, Philipp; Padberg, Laura; Gerstmann, Uwe; Silberhorn, Christine; Eigner, Christof; Schmidt, Wolf Gero (Physical Review Materials)

Time-resolved second-order autocorrelation function of parametric down-conversion - Horoshko, Dmitri B.; Srivastava, Shivang; Sośnicki, Filip Maksymilian; Mikołajczyk, Michał; Karpiński, Michał; Brecht, Benjamin; Kolobov, Mikhail I. (Physical Review A)
We study a possibility of measuring the time-resolved second-order autocorrelation function of one of two beams generated in type-II parametric down-conversion by means of temporal magnification of this beam, bringing its correlation time from the picosecond to the nanosecond scale, which can be resolved by modern photodetectors. We show that such a measurement enables one to infer directly the degree of global coherence of that beam, which is linked by a simple relation to the number of modes characterizing the entanglement between the two generated beams. We illustrate the proposed method by an example of photon pairs generated in a periodically poled potassium titanyl phosphate (KTP) crystal with a symmetric group velocity matching for various durations of the pump pulse, resulting in different numbers of modes. Our theoretical model also shows that the magnified double-heralded autocorrelation function of one beam exhibits a local maximum around zero delay time, corresponding to photon bunching at a short time scale.

Nonreciprocal Metasurfaces with Epsilon-Near-Zero Materials - Mathew, Albert; Aschwanden, Rebecca; Tripathi, Aditya; Jangid, Piyush; Sain, Basudeb; Zentgraf, Thomas; Kruk, Sergey (Nano Letters)
Keywords: metasurfaces; nanophotonics; nonreciprocity; optical isolators; silicon photonics

A novel Lagrangian-based method for the deconvolution of electron energy-loss spectra - Zietlow, Christian
Elektronenenergieverlustspektroskopie (engl. EELS) ist eine fortgeschrittene Analysemethode der Transmissionselektronenmikroskopie, die auf atomarer Ebene Einblicke in Materialcharakteristika wie bspw. Eigenschaften des Elektronensystems oder der Materialzusammensetzung erlaubt. Die Genauigkeit jeder EELS-Analyse ist jedoch fundamental durch Rauschen und Unschärfe begrenzt. Diese Thesis beschreibt solche Rauschphänomene im Detail. Vor allem bei strahlempfindlichen Materialien, die kurze Bestrahlzeiten erfordern, aber auch bei Elektron-Materie-Wechselwirkungen mit geringer Auftrittshäufigkeit, ist eine solche Beschreibung notwendig, da das Rauschen solche Messungen dominiert. Zusätzlich spielen Korrelationen des Rauschens eine Rolle, die durch Faltung des verrauschten Signals mit der Punktspreizfunktion des Detektors entstehen und die sowohl theoretisch als auch experimentell beschrieben werden. Methoden zur Messung der wichtigsten Rauschparameter bei typischen Detektorsystemen werden vorgestellt und erlauben es, das Rauschmodel auf jeden beliebigen EELS-Detektor anzupassen. Eine neue Entfaltungsmethode wird vorgeschlagen, die EELS-Messungen schärft und entrauscht. Die Wirksamkeit dieser Methode wird an Simulations- und Experimentaldaten dargelegt. Hierbei wird gezeigt, dass die neue Methode signifikant bessere Ergebnisse liefert, als bisherige und somit eine Analyse von Messdaten auf einem Level ermöglicht, das die Möglichkeiten der Elektronenmikroskopie deutlich erweitert.

Resonant and antiresonant exciton-phonon coupling in quantum dot molecules - Lienhart, Michelle; Gawarecki, Krzysztof; Stöcker, Markus; Bopp, Frederik; Cullip, Charlotte; Akhlaq, Nadeem; Thalacker, Christopher; Schall, Johannes; Rodt, Sven; Ludwig, Arne; Reuter, Dirk; Reitzenstein, Stephan; et al. (Physical Review B)
Spins confined in optically active quantum dot molecules (QDMs) can be used for the deterministic generation of photonic graph states with tailored entanglement structures. Their usefulness for the generation of such nonclassical states of light is determined by orbital and spin decoherence mechanisms, particularly phonon-mediated processes dominant at energy scales up to a few millielectronvolts. Here, we directly measure the spectral function of orbital phonon relaxation between the energy states of the neutral exciton in a QDM and benchmark our findings against microscopic <a:math xmlns:a="http://www.w3.org/1998/Math/MathML"> <a:mrow> <a:mi mathvariant="bold-italic">k</a:mi> <a:mo>·</a:mo> <a:mi mathvariant="bold-italic">p</a:mi> <a:mspace width="4pt"/> </a:mrow> </a:math> theory. Our results reveal pronounced resonances and antiresonances in the phonon-relaxation rates, ranging from tens of <e:math xmlns:e="http://www.w3.org/1998/Math/MathML"> <e:mrow> <e:mi>µ</e:mi> <e:msup> <e:mrow> <e:mi mathvariant="normal">s</e:mi> </e:mrow> <e:mrow> <e:mo>−</e:mo> <e:mn>1</e:mn> </e:mrow> </e:msup> </e:mrow> </e:math> up to tens of <g:math xmlns:g="http://www.w3.org/1998/Math/MathML"> <g:msup> <g:mrow> <g:mi>ns</g:mi> </g:mrow> <g:mrow> <g:mo>−</g:mo> <g:mn>1</g:mn> </g:mrow> </g:msup> </g:math> . Comparison with a kinetic model reveals the voltage (energy) dependent phonon coupling strength and fully explains the interplay between phonon-assisted relaxation and radiative recombination. The resonances and antiresonances enable further tunability of the exciton lifetime which can be leveraged to increase the lifetime of energetically unfavorable charge configurations needed for realizing efficient spin-photon interfaces and multidimensional cluster states.

Influence of the Etching Material Deposition Rate and Annealing Time on Nanohole Morphology Etched into InP/In0.52Al0.48As Layers via Local Droplet Epitaxy - Deutsch, Dennis; Reuter, Dirk (Crystals)
Local droplet etching and subsequent refilling enables the fabrication of highly symmetric quantum dots with low fine structure splitting, suitable for generating polarization entangled photons. While well established in GaAs/AlxGa1−xAs, this approach does not yield emission in the telecom bands required for low loss fiber-based quantum communication. To achieve emission at 1.55 μm, local droplet etching must be adapted to alternative material platforms such as InP. Here, we systematically investigate how the etching material deposition rate and etching time influence nanohole morphology in In0.52Al0.48As layers lattice-matched to InP. In the first experiment, InAl was deposited at fluxes of 0.2–4.0 Å s−1 at Tetch = 350 °C and 460 °C. Lower fluxes produced nanoholes with lower density and larger ring diameters, indicating fewer and larger initial droplets, consistent with scaling theory. The average nanohole diameter decreased monotonically with increasing flux, whereas the average depth showed no clear dependence on flux. In the second experiment, etching times of 30–600 s were tested for InAl, In, and Al droplets. Average nanohole diameters remained constant for Al across all etching times, but decreased for In and InAl with increasing etching time, suggesting sidewall redeposition during etching. For all droplet types, depths peaked at intermediate times and decreased for prolonged etching, consistent with material diffusion into the nanohole after droplet consumption.

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)

Manipulating spectral topology and exceptional points by nonlinearity in non-Hermitian polariton systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (Physical Review Research, in press)

Photochemical Reaction Enabling the Engineering of Photonic Spin−Orbit Coupling in Organic-Crystal Optical Microcavities - Liang, Qian; Ma, Xuekai; Gu, Chunling; Ren, Jiahuan; An, Cunbin; Fu, Hongbing; Schumacher, Stefan; Liao, Qing (Journal of the American Chemical Society (JACS))

Equivalent-circuit model that quantitatively describes domain-wall conductivity in ferroelectric lithium - Zahn, Manuel; Beyreuther, Elke; Kiseleva, Iuliia; Lotfy, Ahmed Samir; McCluskey, Conor J.; Maguire, Jesi R.; Suna, Ahmet; Rüsing, Michael; Gregg, J. Marty; Eng, Lukas M. (Physical Review Applied)
Ferroelectric domain wall (DW) conductivity (DWC) can be attributed to two separate mechanisms: (a) the injection/ejection of charge carriers across the Schottky barrier formed at the (metal-)electrode-DW junction and (b) the transport of those charge carriers along the DW. Current-voltage (I-U) characteristics, recorded at variable temperatures from LiNbO3 (LNO) DWs, are clearly able to differentiate between these two contributions. Practically, they allow us to directly quantify the physical parameters relevant to the two mechanisms (a) and (b) mentioned above. These are, for example, the resistance of the DW, the saturation current, the ideality factor, and the Schottky barrier height of the electrode-DW junction. Furthermore, the activation energies needed to initiate the thermally activated electronic transport along the DWs can be extracted. In addition, we show that electronic transport along LNO DWs can be elegantly viewed and interpreted in an adapted semiconductor picture based on a double-diode, double-resistor equivalent-circuit model, the R2D2 model. Finally, our R2D2 model was checked for its universality by successfully fitting the I-U curves of not only z-cut LNO bulk DWs, but equally of z-cut thin-film LNO DWs, and of x-cut thin-film DWs as reported in literature.
Keywords: General Physics and Astronomy

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Tailored second harmonic generation inTi-diffused PPLN waveguides usingmicro-heaters - Babai-Hemati, Jonas; vom Bruch, Felix; Herrmann, Harald; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Roadmap on electromagnetic metamaterials and metasurfaces - Cui, Tie Jun; Zhang, Shuang; Alu, Andrea; Wegener, Martin; Pendry, John; Luo, Jie; Lai, Yun; Wang, Zuojia; Lin, Xiao; Chen, Hongsheng; Chen, Ping; Wu, Rui-Xin; et al. (Journal of Physics: Photonics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Dynamics of Electron–Hole Coulomb Attractive Energy and Dipole Moment of Hot Excitons in Donor–Acceptor Polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Derivation of Miller's rule for the nonlinear optical susceptibility of a quantum anharmonic oscillator - Meyer, Maximilian Tim; Schindlmayr, Arno (Journal of Physics B: Atomic, Molecular and Optical Physics)
Miller's rule is an empirical relation between the nonlinear and linear optical coefficients that applies to a large class of materials but has only been rigorously derived for the classical Lorentz model with a weak anharmonic perturbation. In this work, we extend the proof and present a detailed derivation of Miller's rule for an equivalent quantum-mechanical anharmonic oscillator. For this purpose, the classical concept of velocity-dependent damping inherent to the Lorentz model is replaced by an adiabatic switch-on of the external electric field, which allows a unified treatment of the classical and quantum-mechanical systems using identical potentials and fields. Although the dynamics of the resulting charge oscillations, and hence the induced polarizations, deviate due to the finite zero-point motion in the quantum-mechanical framework, we find that Miller's rule is nevertheless identical in both cases up to terms of first order in the anharmonicity. With a view to practical applications, especially in the context of ab initio calculations for the optical response where adiabatically switched-on fields are widely assumed, we demonstrate that a correct treatment of finite broadening parameters is essential to avoid spurious errors that may falsely suggest a violation of Miller's rule, and we illustrate this point by means of a numerical example.

Interdisciplinary approaches between physics and art using the example of optical experiments and artistic light installations - Wolke, Nathalie; Laumann, Daniel; Webersen, Yvonne (Physics Education)

Unbreakable and breakable quantum censorship - Pinske, Julien; Sperling, Jan (Physical Review A)

Measurement of Ultrashort Biphoton Correlation Times with an Integrated Two-Color Broadband SU(1,1)-Interferometer - Roeder, Franz; Pollmann, René; Stefszky, Michael; Santandrea, Matteo; Luo, Kai Hong; Quiring, V.; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
The biphoton correlation time, a measure for the conditional uncertainty in the temporal arrival of two photons from a photon pair source, is a key performance identifier for many quantum spectroscopy applications, with shorter correlation times typically yielding better performance. Furthermore, it provides fundamental insight into the effects of dispersion on the biphoton state. Here, we show that a characteristic dependence of the width of the temporal interferogram can be exploited to obtain insights into the amount of second-order dispersion inside the interferometer and to retrieve actual and Fourier-limited ultrashort biphoton correlation times of around 100 fs. In the presented scheme, we simultaneously measure spectral and temporal interferograms at the output of an SU(1,1) interferometer based on an integrated broadband parametric down conversion source in a Ti:LiNbO3 waveguide.

Certifying the Topology of Quantum Networks: Theory and Experiment - Weinbrenner, Lisa T.; Prasannan, Nidhin; Hansenne, Kiara; Denker, Sophia; Sperling, Jan; Brecht, Benjamin; Silberhorn, Christine; Gühne, Otfried (Physical Review Letters)